2011
DOI: 10.1021/jp110761u
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Modulation Spectroscopy of Single Fluorescent Nanodiamonds with Multiple Nitrogen Vacancy Centers

Abstract: A technique based on polarization modulation spectroscopy (PMS) has been developed to determine quantitatively the number of fluorophores in nanoparticles at the single-molecule level. The technique involves rotation of the polarization of the excitation laser on a millisecond time scale, leading to fluorescence intensity modulation. By taking account of the heterogeneous orientation among the dipoles of the fluorophores and simulating the modulation depth distribution with Monte Carlo calculations, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The results indicate that the angular distribution of a single FND is also quite similar to that of a dipole emitter. The experimental and simulation results confirmed that for a specific configuration, single FNDs can be modeled as a “point dipole emitter” , which is necessary to observe directional emission from the FND and GNR coupled system.…”
Section: Resultssupporting
confidence: 60%
“…The results indicate that the angular distribution of a single FND is also quite similar to that of a dipole emitter. The experimental and simulation results confirmed that for a specific configuration, single FNDs can be modeled as a “point dipole emitter” , which is necessary to observe directional emission from the FND and GNR coupled system.…”
Section: Resultssupporting
confidence: 60%
“…23,117 This defect center absorbs light photons at ∼560 nm and fluoresces brightly at ∼700 nm with a quantum efficiency close to 1. 25,69,120 As such, these centers offer characteristically bright red fluorescence to diamond particles upon excitation with green-yellow light, 22 hence have found applications for high-pressure high-temperature NDs in imaging studies. 19,25 The extreme photostability of (N-V)defect centers 121,122 provides a greater advantage to NDs to emerge as an excellent candidate for long-term cellular imaging over commonly used fluorophores.…”
Section: Nds As Bioimaging Agents Fluorescence Of the Ndsmentioning
confidence: 99%
“…23,117 This defect center absorbs light photons at ∼560 nm and fluoresces brightly at ∼700 nm with a quantum efficiency close to 1. 25,69,120 As such, these centers offer characteristically bright red fluorescence to diamond particles upon excitation with green-yellow light, 22 hence have found applications for high-pressure high-temperature NDs in imaging studies. 19,25 The extreme photostability of (N-V)…”
Section: Nds As Bioimaging Agents Fluorescence Of the Ndsmentioning
confidence: 99%